Displaced people and kidney health - Sanjib Kumar Sharma; Urza Bhattarai; Arun Gautam (Current Opinion in Nephrology & Hypertension, 2026)
Purpose of review The number of displaced people worldwide continues to rise because of conflict and disasters-related crises. Kidney disease is increasingly recognized as an important contributor to morbidity among displaced populations, yet it remains under-prioritized in humanitarian responses. This review summarizes current evidence on the burden, risk factors, barriers, and management of kidney disease in displaced settings. Recent findings Recent literature highlights multiple risk factors linking displacement and kidney disease. Acute kidney injury may result from trauma, dehydration, infections, malnutrition, and environmental exposures, while chronic kidney disease is exacerbated by interrupted care for hypertension and diabetes. Major barriers include disrupted health systems, shortages of dialysis and medications, limited diagnostic capacity, financial constraints, and language and cultural challenges. Reports from Syria, Sudan, Ethiopia, Ukraine, Gaza, and other crisis settings demonstrate substantial treatment interruptions and adverse outcomes among patients requiring dialysis or transplantation. Summary Kidney health should be integrated into humanitarian and primary healthcare responses for displaced populations. Preparedness planning, continuity of care, community-based screening, tele-nephrology, task-shifting, and international collaboration are essential to reduce preventable kidney-related morbidity and mortality. Future research should strengthen epidemiological data and evaluate scalable models of kidney care in displaced settings.